Emma Mourfield: capstone - Mourfield, Emma, artist (Colorado State University. Libraries, 2023)
The artist's statement: Clay is a material that has a strong connection to the body, making it important for me to emphasize process and hand work within my practice. Because clay is inherently malleable, each touch creates a physical memory of the artist's hand. This bodily connection is shown within my work through focus on small details and finishings, instilling an intimate sense of personal touch in each piece. In order to further the personal connection between the medium and self, I often reflect my own style and autobiographical narrative into the pieces that I create. Using stoneware, porcelain, and casting slip, my work ranges from traditional wheel thrown pottery to slip casted sculptures. Within my body of work, I touch on subjects of form, beauty, design, self reflection/image, control, irreverence, humor, and play.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery